1993
DOI: 10.1088/0953-8984/5/17/007
|View full text |Cite
|
Sign up to set email alerts
|

Formation of disordered structures in Cr-Fe alloy by mechanical milling

Abstract: Mechanical milling was performed on the alloy CrnFeB. X-ray diFSraction and Mlissbauer spectmscopy were used IO follow the progress of the shuctural variation. The experimental results can be interpreted by assuming that the milled powden are composed of a small amount of crystalline component and two disordered components: one with a &om densely packed shucLure and the 0 t h with a random lwsely packed structure. Moreover, differential scanning d o r i m e y was used to obIain the crystallization temperature.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
22
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 17 publications
5
22
0
Order By: Relevance
“…Thus, we attribute the central peak of the Mössbauer spectra to an amorphous phase with an average isomer shift of −0.08(2) mm/s in agreement with the results of Xia et al [13].…”
Section: Methodssupporting
confidence: 91%
See 1 more Smart Citation
“…Thus, we attribute the central peak of the Mössbauer spectra to an amorphous phase with an average isomer shift of −0.08(2) mm/s in agreement with the results of Xia et al [13].…”
Section: Methodssupporting
confidence: 91%
“…Further, a contamination by steel coming from milling tools would contribute to a Fe-enrichment of the milled powders and thus to an increase of the measured magnetic moment. At least two assumptions can be put forward to explain a magnetisation decrease: (a) the formation of an amorphous phase [12,13], which is non-magnetic in the studied concentration range and is possibly favoured by the presence of oxygen in ball-milled alloys [14]; (b) a phase separation with a significant amplitude which is difficult to evidence by X-ray diffraction in such alloys.…”
Section: Introductionmentioning
confidence: 99%
“…The relative spectral areas of M and P sub spectra are marked by A, and the average isomer shift by <IS> (relative to the -Fe). It is observed that the shape and the range of QS-values seen in the presently determined QSD histograms agree well with those previously reported [15,16,21] for amorphous Fe-Cr alloys. From the data displayed in Table 2 one can see that the abundances of the M-phases agree fairly well with the intensities of the narrow diffraction peak, while those of the P-phases are in line with the intensities of the broad XRD peak.…”
Section: Mössbauer Spectroscopysupporting
confidence: 90%
“…For Fe-Cr alloys, several studies conducted by ball milling showed their amorphization e.g. [13][14][15][16][17][18][19][20][21]. In particular, in equiatomic or near-equiatomic FeCr alloys milled in vacuum or argon atmosphere, this effect was observed both in alpha and sigma phases, e.g.…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, iron and near-equiatomic Fe-Cr alloys were shown to be sensitive to the presence of gases when ground in high-energy ball-mills [20][21][22][23][24][25][26][27][28][29]. Rawers et al [20][21][22] compared the microstructures of ␣-Fe ground in argon and in nitrogen in a Szegvari type attrition mill.…”
Section: E-mail Address: Benilde@ciucpt (Bfo Costa)mentioning
confidence: 99%